2014
DOI: 10.1002/2327-6924.12036
|View full text |Cite
|
Sign up to set email alerts
|

The effect of breastfeeding on childhood overweight and obesity: A systematic review of the literature

Abstract: Background Childhood obesity has reached epidemic proportions. There is increasing attention to the topic of prevention and continued debate as to whether breastfeeding (BF) is protective against childhood obesity. Previous systematic reviews on this topic were done in 2005 showing that BF was protective against childhood obesity but, because of confounding variables, the evidence was weak. Objective To explore the current evidence of the effect of BF on childhood obesity and provide recommendations for the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 43 publications
2
36
0
4
Order By: Relevance
“…3). Breastfeeding has been shown to significantly reduce the risk of overweight/ obesity later in childhood as well as in adult life (68); however, conflicting reports of the role of breastfeeding in obesity also exist (69). We speculate that the observation that continued breastfeed- Table 1. ing at 9 months delays progression of specific bacterial taxa may be of relevance for development and later-life health.…”
Section: Resultsmentioning
confidence: 93%
“…3). Breastfeeding has been shown to significantly reduce the risk of overweight/ obesity later in childhood as well as in adult life (68); however, conflicting reports of the role of breastfeeding in obesity also exist (69). We speculate that the observation that continued breastfeed- Table 1. ing at 9 months delays progression of specific bacterial taxa may be of relevance for development and later-life health.…”
Section: Resultsmentioning
confidence: 93%
“…Dietary variables were collected during pregnancy for mothers and annually at 2–5 years of age for children. We adjusted for prenatal vitamin use and breastfeeding duration because vitamins may be a source of methyl donors, and breastfeeding may decrease child obesity risk, respectively (Anderson et al 2012; Lefebvre and John 2014). Child activity variables were collected annually at 2–5 years of age and included parent-reported hours of daily television watching and outdoor time.…”
Section: Methodsmentioning
confidence: 99%
“…Colen et al 24 stated that desirable health effects originally attributed to breast feeding, may be due to other key characteristics, such as ethnicity and socioeconomic status. A recent review concluded that the beneficial effect of breast feeding on childhood obesity is difficult to prove because of confounding variables 25. Both studies emphasise the role of confounders.…”
Section: Discussionmentioning
confidence: 99%